Proceedings of the 24th ACM Symposium on Virtual Reality Software and Technology 2018
DOI: 10.1145/3281505.3281519
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chair type on users' viewing experience for 360-degree video

Abstract: The consumption of 360-degree videos with head-mounted displays (HMDs) is increasing rapidly. A large number of HMD users watch 360-degree videos at home, often on non-swivel seats; however videos are frequently designed to require the user to turn around. This work explores how the dierence in users' chair type might inuence their viewing experience. A between-subject experiment was conducted with 41 participants. Three chair conditions were used:xed, half-swivel and full-swivel. A variety of measures were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In [25], the effect of fixed, half-swivel, and full-swivel chairs on users' viewing experience of 360 • videos on a FOVE-DK-0 HMD with a resolution of 2560 × 1440 pixels was investigated. Eye-tracking, questionnaires, tasks, and semi-structured interviews were used in a between-subject experiment in which participants were shown one training and five 360 • test videos of 4K resolution.…”
Section: Viewing Conditions and Users' Viewing Experience In Vrmentioning
confidence: 99%
“…In [25], the effect of fixed, half-swivel, and full-swivel chairs on users' viewing experience of 360 • videos on a FOVE-DK-0 HMD with a resolution of 2560 × 1440 pixels was investigated. Eye-tracking, questionnaires, tasks, and semi-structured interviews were used in a between-subject experiment in which participants were shown one training and five 360 • test videos of 4K resolution.…”
Section: Viewing Conditions and Users' Viewing Experience In Vrmentioning
confidence: 99%
“…Besides VR sickness and user comfort, another metric of interest in this study is the path integration of the user, which should not deteriorate when unwinding rotations, since disorientation can cause anxiety and discontent [27]. Studies related to ours show that physical rotation increased spatial awareness (which correlates with path integration) over moving with a joystick [28] and a sviwel chair increases spatial awareness over a fixed chair [29]. In this study we do not explicitly tell the users to rotate themselves along with the robot while watching the videos, but they do sit in a swivel chair making it easily possible.…”
Section: Related Workmentioning
confidence: 85%
“…For example, Hong and colleagues (2018) showed that if the user was engaging with VR whilst sitting in a chair, the type of chair affected their overall experience. More speci cally, users in xed and half-swivel chairs had worse spatial immersion and greater concern about missing part of the VE and the storyline (Hong et al 2018).…”
Section: Environmentmentioning
confidence: 99%